A constructivist didactics framework for e-collaboration through social media. (2015) - Yussiff, Alimatu-Saadia; Ahmad, Wan Fatimah Wan; Mustapha, Emy Elyanee
E-learning since 1990s is still evolving. Currently, there is a shift towards e-collaborative teaching and learning approaches. Despite this shift, there is still a gap between constructivist online teaching and learning and actual practices in higher educational institutions. The objective of this paper is to propose a constructivist didactic framework for e-collaboration for higher educational institutions. The methodologies employed include an exploratory and explanatory study of prior related concepts, theories and frameworks. These were followed by keywords identifications, brainstorming, selections and iteration. Results indicated that the five learning theories studied support collaboration have overlapping design principles and didactics methods. Findings from the nine frameworks studied also presented some useful elements integrated into the framework. On the whole, the derived framework integrates iterative development process, users' roles, collaboration process, evaluation tools, and social media for synchronous and asynchronous collaborations. The comprehensive nature of the resulting framework is clear enough to guide research.